Response of isotopically tailored titanium diboride to neutron irradiation. Issue 1 (10th September 2018) - Koyanagi, Takaaki; Katoh, Yutai; Ang, Caen; King, Derek; Hilmas, Greg E.; Fahrenholtz, William G.
Abstract: The response of polycrystalline TiB2 to neutron irradiation was investigated. The material was fabricated using isotopically enriched 11 B powders to minimize helium production via the 10 B(n, α) 7 Li reaction. Neutron irradiation was conducted at temperatures of 200°C and 600°C to a fast fluence of 2.4 × 10 25 n/m 2 (>0.1 MeV). The material exhibited some swelling, but less swelling at the higher irradiation temperature. No macroscopic damage was observed in the irradiated material, although moderate irradiation‐induced micro‐cracking was found in the irradiated TiB2 . This study demonstrated improved radiation resistance of isotopically tailored TiB2 compared with natural boron TiB2, which exhibited macroscopic fracture by irradiation.